Nanoporous thermochromic VO2 (M) thin films : controlled porosity, largely enhanced luminous transmittance and solar modulating ability - Cao, Xun (2014)
Vanadium dioxide is the most widely researched thermochromic material with a phase transition temperature (τc) of around 68 °C, and its thermochromic performance can be enhanced by adding nanoporosity. Freeze-drying has been employed to fabricate nanostructures with different porosities from 16 to 45% by varying the prefreezing temperature and precursor concentration. The luminous transmittance (Tlum) and solar modulating ability (ΔTsol) are greatly enhanced as a result of increasing pore size and pore density. The freeze-dried sample with 7.5 mL of H2O2 precursor dip-coated at 300 mm/min gives the best combination of thermochromic properties (Tlum ≈ 50%, ΔTsol = 14.7%), which surpasses the best combined thermochromic performance reported to date that we are aware of (Tlum ≈ 41%, ΔTsol = 14.1%).